Початки наукового зацікавлення українським фольклором (збирання і вивчення) - Кирчів, Р. (Народна творчість та етнографія, 2006)
The article speaks on the formation of Ukrainian folklore studies. The author mentions the first steps made in the researches of the 18th-19th centuries. Historical-literary essay of unknown writer "The History of Ruses" and its specific features arc depicted in the article. The author researches several scholars of that time and their collections of folklore. A part of the article is dedicated to folklore activities of Mykola Tsertelev. whose love of Ukrainian folklore ran into the first printed edition of folk dumy. the work that brought new views on the folklore studies.